Control of the Estrus Cycle Using Different Doses of the PGF2α Hormone in Kacang Goats - Yamonaha Gea; Jusak Labetubun; Isak P. Siwa (Universitas Pattimura, 2023)
The purpose of this research is to determine the effectiveness of giving doses of the hormone PGF2α to control the estrus cycle in kacang goats. This research was conducted at Air Ali hamlet and Waringin Cap hamlet for 1 (one) month, starting from October 2022 to November 2022. The method used in this study was the experimental method with 2 doses of the hormone PFG2α, namely 0.6 ml (P1) and 0.5 ml (P2) for 8 goats (each treatment consisted of 4 replications). The female goat used was 3-4 years old and had given birth to one child. The results showed that the duration of estrus at P1 and P2 was not different (P < 0.05) but 100% of goats that were treated both at P1 and at P2 showed the same estrus symptoms with the following characteristics; cattle are restless, make a distinctive sound and move their tail, urinate frequently, their vulva is red and looks swollen, and feels warm when toucher and likes to be held by others. The research concluded that a dose of 0.5 ml of hormone was still effective for synchronizing lust in peanut goats.